Empoderamento dos catadores em organizações coletivas:uma análise a partir da percepção de presidentes de associações e cooperativas na microrregião de Toledo - Maas, Tainara Ianka (2022)
The present work includes a study that aims to assess the existence or not of an empowerment process among the class of solid waste collectors in the 21 municipalities of the Microregion of Toledo, in the west of Paraná. Therefore, through an accurate bibliographical review, we started with a historical retrospective about how the concept of empowerment emerged, analyzing the different meanings linked to this term, as well as the two dimensions in which it is subdivided: political and psychological. Furthermore, the origin of the waste picker class was also researched, also evaluating how society has dealt with garbage throughout history. Following the qualitative research model, with semi-structured interviews, a series of surveys was carried out with the presidents of waste pickers associations in the cities included in the aforementioned region. Taking, as a sample, the presidents of the four oldest associations – Assis Chateaubriand, Santa Helena, Toledo and Entre Rios do Oeste – the time lines of such individuals were examined, proving that, in all of them, there was a process of evolution in political and psychological aspects, which characterizes a legitimate state of empowerment. This sample, added to other information obtained in interviews with members of other associations, proved that collectors, once organized into associations, are better able to establish partnerships with governmental and non-governmental organizations, enabling them to obtain financial and intellectual contributions. As a result, such subjects tend to rise to a condition of empowerment, ensuring the achievement of rights as citizens and, above all, social recognition.